Analysis of Administration of Regional Property Based on Minister of Home Affairs Regulation No. 47 of 2021 at the North Sulawesi Province Industry And Trade Service - Takasenseran, Angelina Aurelia; Morasa, Jenny; Sardjono, Olivia Y. M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to find out the Administration of Regional Property Based on Administration No. 47 of 2021 at the North Sulawesi Provincial Departement of Industry and Trade. The data analysis method used is descriptive qualitative research, namely with a descriptive approach. The result of the study show that the implementation of the administration of Regional Property (BMD) at the North Sulawesi Provinscial Departement of Industry and Trade has shown efforts to comply with the Regulation of the Minister of Home Affairs Number 47 of 2021. In the aspect of bookkeeping and invetory, the Provincial Disperindag. North Sulawesi has implemented procedures in accordance with regulations, including the use of the e-BMD application to improve the accuracy and efficiency of data management.